A pandemic lesson for global lung diseases: exacerbations are preventable. - Cookson,W; Moffatt,M; Rapeport,G; Quint,J (American Journal of Respiratory and Critical Care Medicine, 2022)
A dramatic global reduction in the incidence of common seasonal respiratory viral infections has resulted from measures to limit the transmission of SARS2-Cov-19 during the pandemic . This has been accompanied by falls reaching 50% internationally in the incidence of acute exacerbations of pre-existing chronic respiratory diseases that include asthma, Chronic Obstructive Pulmonary Disease (COPD) and Cystic Fibrosis (CF). At the same time, the incidence of acute bacterial pneumonia and sepsis has fallen steeply world-wide. Such findings demonstrate the profound impact of common respiratory viruses on the course of these global illnesses. Reduced transmission of common respiratory bacterial pathogens and their interactions with viruses appear also as central factors. This review summarises pandemic changes in exacerbation rates of asthma, COPD, Cystic Fibrosis (CF) and pneumonia. We draw attention to the substantial body of knowledge about respiratory virus infections in these conditions, and that it has not yet translated into clinical practice. Now the large-scale of benefits that could be gained by managing these pathogens is unmistakable, we suggest the field merits substantial academic and industrial investment. We consider how pandemic-inspired measures for prevention and treatment of common infections should become a cornerstone for managing respiratory diseases. This article is open access and distributed under the terms of the Creative Commons Attribution Non-Commercial No Derivatives License 4.0 (http://creativecommons.org/licenses/by-nc-nd/4.0/).